Diagnostic accuracy of VIKIA® Rota-Adeno and Premier™ Rotaclone® tests for the detection of rotavirus in Niger - Lagare, Adamou (BMC Res Notes, 2017)
OBJECTIVE: We conducted a parallel evaluation of the diagnostic accuracy of VIKIA® Rota-Adeno, a rapid diagnostic test (RDT) and Premier™ Rotaclone® an enzyme immunoassay (EIA) using reverse transcription polymerase chain reaction (RT-PCR) as the reference standard. The study was part of a rotavirus surveillance project in Niger. RESULTS: The sensitivity of both tests was 80.7%. After exclusion of one indeterminate result by visual reading, the specificity of the Premier™ Rotaclone® was 100% by visual or optical density readings and that of VIKIA® Rota-Adeno test was 95.5%. Inter-reader agreement was excellent for both tests (kappa = 1). Our results showed almost similar performance of the EIA and RDT when compared to RT-PCR. Hence, the VIKIA® Rota-Adeno could be a good alternative for use in peripheral health centres where laboratory capacity is limited.